A systems biology approach identifies the role of dysregulated PRDM6 in the development of hypertension - Kushan L. Gunawardhana; Lingjuan Hong; Trojan Rugira; Severin Uebbing; Joanna Kucharczak; Sameet Mehta; Dineth R. Karunamuni; Brenda Cabera-Mendoza; Neeru Gandotra; Curt Scharfe; Renato Polimanti; James P. Noonan; et al. (The Journal of Clinical Investigation, 2023)
Genetic variants in the third intron of the PRDM6 gene have been associated with BP traits in multiple GWAS. By combining fine mapping, massively parallel reporter assays, and gene editing, we identified super enhancers that drive the expression of PRDM6 and are partly regulated by STAT1 as the causal variants for hypertension. The heterozygous disruption of Prdm6 in mice expressing Cre recombinase under the control of mouse smooth muscle cell protein 22-α promoter (Prdm6fl/+ SM22-Cre) exhibited a markedly higher number of renin-producing cells in the kidneys at E18.5 compared with WT littermates and developed salt-induced systemic hypertension that was completely responsive to the renin inhibitor aliskiren. Strikingly, RNA-Seq analysis of the mouse aortas identified a network of PRDM6-regulated genes that are located in GWAS-associated loci for blood pressure, most notably Sox6, which modulates renin expression in the kidney. Accordingly, the smooth muscle cell–specific disruption of Sox6 in Prdm6fl/+ SM22-Cre mice resulted in a dramatic reduction of renin. Fate mapping and histological studies also showed increased numbers of neural crest–derived cells accompanied by increased collagen deposition in the kidneys of Prdm6fl/+ Wnt1Cre-ZsGreen1Cre mice compared with WT mice. These findings establish the role of PRDM6 as a regulator of renin-producing cell differentiation into smooth muscle cells and as an attractive target for the development of antihypertensive drugs.